2022
DOI: 10.1177/09544062221097804
|View full text |Cite
|
Sign up to set email alerts
|

Deformation prediction and compensation of a dual-machine riveting system for aircraft assembly

Abstract: Automatic riveting systems play a crucial role in the field of aircraft manufacturing. In the riveting process, the machine tool bears a large axial squeezing force, and the resulting deformation will inevitably affect the riveting quality. In this paper, a dual-machine riveting system is developed first, the kinematic chain model and the lower-numbered body of the system structure are constructed sequentially. Then, considering the interaction and coupling effect of the two machines in the actual riveting pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…[14][15][16] FEM analyses of composite materials mainly output the lamina stress state, equivalent modulus of elasticity, as well as elongation. [15][16][17][18] However, FEM studies are also indispensable for fracture prediction (some examples can be found in Vasiliev and Morozov, 19 Wang et al, 21 and Svorcan et al 22 ). Physically, two types of failures can occur at composite materials, that is intralaminar and interlaminar failures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16] FEM analyses of composite materials mainly output the lamina stress state, equivalent modulus of elasticity, as well as elongation. [15][16][17][18] However, FEM studies are also indispensable for fracture prediction (some examples can be found in Vasiliev and Morozov, 19 Wang et al, 21 and Svorcan et al 22 ). Physically, two types of failures can occur at composite materials, that is intralaminar and interlaminar failures.…”
Section: Introductionmentioning
confidence: 99%
“…Research 9 demonstrated excellent correspondence between numerical and experimental testing of material characteristics and verified the chosen manufacturing technique. 1416 FEM analyses of composite materials mainly output the lamina stress state, equivalent modulus of elasticity, as well as elongation. 1518 However, FEM studies are also indispensable for fracture prediction (some examples can be found in Vasiliev and Morozov, 19 Wang et al, 21 and Svorcan et al 22 ).…”
Section: Introductionmentioning
confidence: 99%